Cisplatin-induced nephrotoxicity in mice: protective role of Leea asiatica leaves. (3rd September 2013) - Sen, Saikat; De, Biplab; Devanna, N.; Chakraborty, Raja
Abstract: Cisplatin is a popular anticancer drug, but its side effects like nephrotoxicity and hepatotoxicity due to oxidative stress limited its clinical use. In tis study, nephoprotective effect of fractions of Leea asiatica (Leeaceae) leaves was assessed against cisplatin induced toxicity in rats. Leaves of L. asiatica extracted with methanol, ethyl acetate, petroleum ether, and evaluated for in vitro and ex vivo antioxidant activity using several assay models. Methanol extract showed better antioxidant effects, and contain higher amount of phenolic (77.75 ± 0.87 mg GAE/g of dry material) and flavonoid compound (60.98 ± 0.58 mg QE/g of dry material) compared with other extracts. Hance methanol extract was selected for further investigation and fractionated with methanol, ethyl acetate, petroleum ether. Protective effect of methanol extract and its fractions was evaluated against cisplatin (20 mg/kg, i.p.) induced nephrotoxicity. Pretreatment with methanol extract (150 and 300 mg/kg), and its fractions especially methanol, ethyl acetate fraction (75 and 150 mg/kg) significantly reduced blood urea nitrogen, serum creatinine, uric acid levels, and decreased malondialdehyde level and increase total protein and albumin level ( p  < 0.05, 0.01). Ethyl acetate fraction produced highest nephroprotective, possibly by inhibiting lipid peroxidation process. Result suggested that ethyl acetate fraction possesses potent nephroprotective activity and can be used an adjunct therapy aiming to improve the effectiveness of several nephrotoxic drugs.